Juridical Analysis of the State Administrative Court of Surabaya’s Decision No. 32/G/2023/PTUN.SBY on Land Ownership Certificate Overlapping - Sarjiyati Sarjiyati; Angga Pramodya Pradhana; Anik Tri Haryani; Bambang Sukarjono; Izyana Farhana Zulkarnain; Galuh Ayu Rahmawati (Jurnal Jurisprudence, 2024)
ABSTRACT  Purpose of the Study: This research aims to analyze the State Administrative Court of Surabaya City judges’ basis of consideration in Decision No. 32/G/2023/PTUN.SBY in resolving the dispute of land ownership certificate overlapping through the litigation method and knowing the legal consequences of this decision. Methodology: This research employed the normative legal research method. The data were descriptively analyzed to obtain research results. It used applicable court decisions, legal regulations and the general principle of good governance as its basis of consideration. Results: In its relations with the Plaintiff's lawsuit, Judge Assembly stated that it had fulfilled the lawsuit’s formal aspect on deadlines in issuing the certificate which is the Defendant’s authority. However, in the issue of procedures and substances, there have been deviations that violate the applicable legal regulations and the general principle of good governance. Based on the author’s analysis, these judges have given accurate considerations. The legal consequences of State Administrative Court of Surabaya City's Decision No. 32/G/2023/PTUN.SBY are that the two land tenure certificates owned by Defendant II Intervention were revoked by Surabaya City's State Administrative Court. Apart from that, the Defendant and Defendant II Intervention are burdened with paying for the case fees. Applications of this study: This research becomes a reference for National Land Agency Officers to be more careful when issuing certificates to prevent administrative and/or juridical errors. Novelty/Originality of this study: This research analyzed the decision of Surabaya City’s State Administrative Court on the revocation of 2 (two) land ownership certificates issued by the Batu City Land Agency and the legal consequences of State Administrative Court of Surabaya City’s Decision No. 32/G/2023/PTUN.SBY. Keywords: Decision, overlapping, land tenure certificates, dispute resolution   ABSTRAK Tujuan Penelitian: Penelitian ini bertujuan untuk menganalisis dasar pertimbangan hakim Pengadilan Tata Usaha Negara Kota Surabaya dalam Putusan Nomor 32/G/2023/PTUN.SBY dalam menyelesaikan sengketa tumpang tindih sertifikat hak milik atas tanah melalui metode litigasi dan mengetahui akibat hukum dari putusan tersebut. Metodologi: Penelitian ini menggunakan metode penelitian hukum normatif. Data dianalisis secara deskriptif untuk memperoleh hasil penelitian. Dasar pertimbangan yang digunakan adalah putusan pengadilan yang berlaku, peraturan perundang-undangan, dan asas umum pemerintahan yang baik. Hasil: Terkait gugatan Penggugat, Majelis Hakim menyatakan telah memenuhi aspek formil gugatan mengenai batas waktu penerbitan sertifikat yang merupakan kewenangan Tergugat. Namun, dalam masalah prosedur dan substansi masih terdapat penyimpangan yang melanggar peraturan perundang-undangan yang berlaku dan asas umum pemerintahan yang baik. Berdasarkan analisis penulis, para hakim telah memberikan pertimbangan yang tepat. Akibat hukum dari Putusan PTUN Kota Surabaya Nomor 32/G/2023/PTUN.SBY adalah dua sertifikat hak milik atas tanah milik Tergugat II Intervensi dicabut oleh PTUN Kota Surabaya. Selain itu, Tergugat dan Tergugat II Intervensi dibebani biaya perkara. Aplikasi penelitian ini: Penelitian ini menjadi acuan bagi Pejabat Badan Pertanahan Nasional agar lebih cermat dalam menerbitkan sertifikat untuk mencegah terjadinya kesalahan administratif dan/atau yuridis. Kebaruan/Orisinalitas penelitian ini: Penelitian ini menganalisis putusan PTUN Kota Surabaya atas pencabutan 2 (dua) sertifikat hak milik atas tanah yang diterbitkan oleh Badan Pertanahan Kota Batu dan akibat hukum dari Putusan PTUN Kota Surabaya Nomor 32/G/2023/PTUN.SBY. Kata kunci: Putusan, tumpang tindih, sertifikat hak milik atas tanah, penyelesaian sengketa